The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1111/j.1439-0450.1991.tb00844.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of BHV‐1 Variants by In Vivo — In Vitro Tests

Abstract: The new encephalitogenic BHV-1.3 and previously characterized BHV-1 strains were studied with reference to their immunogenic and protective potency and their antigenic relationships using "in vitro" and "in vivo" tests.The "in vitro" results obtained by neutralization kinetics showed that the Los Angeles (LA) strain (BHV-1.1) and a vaginal isolate L-114 strain (BHV-1.2) had antigenic similarities. Conversely, the behavior of the encephalitogenic strain A-663 (BHV-1.3), was significantly distinct.' The "in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
13

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 19 publications
1
24
0
13
Order By: Relevance
“…O BHV-5, por sua vez, causa encefalites ou meningoencefalites, usualmente afetando animais até oito meses de idade, embora ocasionalmente envolvendo animais mais velhos, com baixa morbidade e alta mortalidade (French 1962, Bulach & Studdert 1990, Salvador et al 1998. Até recentemente, amostras de BHV-5 eram consideradas "variantes encefalitogê-nicas" de BHV-1, devido às amplas reações cruzadas entre os dois vírus detectadas em testes sorológicos (Bratanich et al 1991, Teixeira et al 1998. Entretanto, as características epidemiológicas distintas destas infecções, amparadas em estudos antigênicos e moleculares, levaram à criação do tipo 5 para enquadrar este "novo" agente encefalitogênico em um taxon diferente (Roizman et al 1992).…”
Section: Introdução Introdução Introdução Introdução Introduçãounclassified
“…O BHV-5, por sua vez, causa encefalites ou meningoencefalites, usualmente afetando animais até oito meses de idade, embora ocasionalmente envolvendo animais mais velhos, com baixa morbidade e alta mortalidade (French 1962, Bulach & Studdert 1990, Salvador et al 1998. Até recentemente, amostras de BHV-5 eram consideradas "variantes encefalitogê-nicas" de BHV-1, devido às amplas reações cruzadas entre os dois vírus detectadas em testes sorológicos (Bratanich et al 1991, Teixeira et al 1998. Entretanto, as características epidemiológicas distintas destas infecções, amparadas em estudos antigênicos e moleculares, levaram à criação do tipo 5 para enquadrar este "novo" agente encefalitogênico em um taxon diferente (Roizman et al 1992).…”
Section: Introdução Introdução Introdução Introdução Introduçãounclassified
“…In these countries, BoHV-1-based vaccines have been increasingly used in the last decades, and only a few vaccines have been formulated that contain both BoHV-1 and BoHV-5 strains. BoHV-1 and -5 show extensive serological cross-reactivity so that they cannot be distinguished by routine virus neutralization tests (32). In addition, it has been demonstrated that a BoHV-1 vaccine induced partial protection against a BoHV-5 virulent challenge in calves (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the differences in the envelope glycoproteins, the traditional serological techniques and the majority of BHV-1 and BHV-5 monoclonal antibodies (mAbs) are unable to distinguish between these two viruses (16,17). Likewise, extensive serological cross-reactivity has been demonstrated between BHV-1 and BHV-5 (17)(18)(19). Nevertheless, the occurrence of cross-protection between BHV-1 and BHV-5 is still controversial (8,17,(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, extensive serological cross-reactivity has been demonstrated between BHV-1 and BHV-5 (17)(18)(19). Nevertheless, the occurrence of cross-protection between BHV-1 and BHV-5 is still controversial (8,17,(19)(20)(21)(22). A possible cross-protection between these viruses would be of obvious interest for immunization strategies and vaccine production since only BHV-1 vaccines are available to date (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation